PENINGKATAN KREATIVITAS DAN HASIL BELAJAR SISWA MELALUI PENDEKATAN KONTEKSTUAL DI KELAS V SEKOLAH DASAR - Fajar Dwi Mukti (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
The aims of this study are: To increase creativity and learning outcomes through a contextual approach in class V of elementary school. This type of research is a class action research of 2 cycles. Each cycle consists of 4 stages, namely planning, implementation of action, observation and reflection. The research subjects were fifth grade elementary school students. Data collection techniques using observation, interviews, documentation and tests. There is an increase in student creativity as indicated by an increase in student attitudes when participating in learning in each cycle. In cycle I with a percentage of 66.5% including sufficient criteria. In cycle II, a percentage of 84.5% was obtained with good creativity criteria. Student learning outcomes can be seen from the mastery of student learning in cycle I with an average score of 65.2 and 60% mastery of learning, then in cycle II it increases with an average value of 82 and 90% of learning completeness. contextual can increase creativity and learning outcomes through a contextual approach in grade V elementary school.